Foot-and-Mouth Disease Virus Counteracts on Internal Ribosome Entry Site Suppression by G3BP1 and Inhibits G3BP1-Mediated Stress Granule Assembly via Post-Translational Mechanisms - Ye, Xu; Pan, Ting; Wang, Dang; Fang, Liurong; Ma, Jun; Zhu, Xinyu; Shi, Yanling; Zhang, Keshan; Zheng, Haixue; Chen, Huanchun; Li, Kui; Xiao, Shaobo (Frontiers in Immunology, 2018)
Foot-and-mouth disease (FMD) is a highly contagious, severe viral illness notifiable to the World Organisation for Animal Health. The causative agent, FMD virus (FMDV), replicates rapidly and efficiently inhibits host translation and the innate immune response for it has developed multiple tactics to evade host defenses and takes over gene expression machinery in the host cell. Here, we report a systemic analysis of the proteome and phosphoproteome of FMDV-infected cells. Bioinformatics analysis suggested that FMDV infection shuts off host cap-dependent translation, but leaves intact internal ribosome entry site (IRES)-mediated translation for viral proteins. Interestingly, several FMDV IRES-transacting factors, including G3BP stress granule assembly factor 1 (G3BP1), were dephosphorylated during FMDV infection. Ectopic expression of G3BP1 inhibited FMDV IRES activity, promoted assembly of stress granules, and activated innate immune responses, collectively suppressing FMDV replication. To counteract these host protective responses, FMDV induced dephosphorylation of G3BP1, compromising its inhibitory effect on viral IRES. In addition, FMDV also proteolytically cleaved G3BP1 by its 3C protease (3Cpro). G3BP1 was cleaved at Glutamic acid-284 (E284) by FMDV 3Cpro, and this cleavage completely lost the abilities of G3BP1 to activate innate immunity and to inhibit FMDV replication. Together, these data provide new insights into the post-translational mechanisms by which FMDV limits host stress and antiviral responses and indicate that G3BP1 dephosphorylation and its proteolysis by viral protease are important factors in the failure of host defense against FMDV infection.